2010
DOI: 10.1016/j.medin.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

El papel del catéter de Swan-Ganz en la actualidad

Abstract: Nearly forty years ago, Swan and Ganz introduced pulmonary artery catheterization to monitor the hemodynamic status of critical patients. The need for pulmonary artery catheterization in clinical practice has been questioned because it may be related to increased mortality and because alternative techniques that will probably cause less morbidity and mortality have been developed. The introduction of color Doppler echocardiography has been fundamental in the hemodynamic and etiologic evaluation of critical pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 114 publications
0
7
0
6
Order By: Relevance
“…12 The limitations of measurement of cardiac output by transpulmonary thermodilution are: a) thermal variations since there may be thermal artefacts that involve distortion in the thermodilution curve; b) when the patient undergoes extracorporeal purification treatments, the blood is directed to a recirculation path of the thermal indicator and also of artifact; c) intracardiac shunts, due to the distortion on the morphology of the transpulmonary thermodilution curve. 13 A wide variety of methods are currently available to monitor the GC with important differences between them. These devices can be classified according to the degree of invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…12 The limitations of measurement of cardiac output by transpulmonary thermodilution are: a) thermal variations since there may be thermal artefacts that involve distortion in the thermodilution curve; b) when the patient undergoes extracorporeal purification treatments, the blood is directed to a recirculation path of the thermal indicator and also of artifact; c) intracardiac shunts, due to the distortion on the morphology of the transpulmonary thermodilution curve. 13 A wide variety of methods are currently available to monitor the GC with important differences between them. These devices can be classified according to the degree of invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…11 In clinical practice, the most common way to evaluate afterload is by calculating the systemic or pulmonary vascular resistance (VR), which offers information on vascular tone. 12 It is important to take into account that the arterial VR value only represents opposition or resistance to a constant flow, which is found fundamentally at arteriolar level, where the compensating mechanisms that control vasomotor tone keep the perfusion pressure within a physiological range. In this context, a complete description of global arterial impedance is not provided, due to the fluctuating nature of blood flow and arterial pressure.…”
Section: Afterloadmentioning
confidence: 99%
“…It now moreover offers the possibility of incorporating electrocatheters positioned in the right atrium and ventricle. 12 At present, controversy over the use of the pulmonary artery catheter and the technological advances of recent years have led to the development of new hemodynamic monitorization systems that also offer us some of these ''old'' parameters and at the same time are able to determine ''new'' cardiovascular function parameters (Table 1). Traditionally, the parameter most widely used in the ICU for evaluating ventricular function has been cardiac output (stroke volume × heart rate).…”
Section: Parameters Derived From Classical Hemodynamicsmentioning
confidence: 99%
“…---High-risk postsurgical patients: In high surgical risk patients, it has been shown that adequate optimization of cardiac output and of oxygen extraction (DO 2 ) during the operation 31 and in the hours immediately after surgery 32 has a direct beneficial impact upon the prognosis, with fewer complications and a shortening of hospital stay. 33 ---Cardiogenic shock: A situation in which the exhaustive monitorization of cardiac output is particularly important as part of the initial patient monitorization protocol is suspected myocardial dysfunction as the primary cause of the critical condition. Cardiogenic shock may be caused by structural alterations of the heart (e.g., coronary disease) or may be secondary to other processes (e.g., massive pulmonary thromboembolism, drug-related myocardial depression).…”
Section: When To Monitor Cardiac Outputmentioning
confidence: 99%